Politics of Belonging: Being Armenian in Turkey and Lebanon - Ertekin, Pinar (AUC Knowledge Fountain, 2023)
An estimated two million Armenians lived in the Ottoman Empire before the beginning of World War I, and almost all of them were annihilated or displaced during the genocide of 1915. My work revolves around the meaning of the Armenian Genocide to Armenians living in Turkey and Lebanon. I focused on what it feels like to be an Armenian living as a Turkish citizen in a state and nation that had perpetuated and then consistently denied the genocide of their ancestors, and I examined how Armenians in Turkey experience their everyday lives, the challenges they encounter as well as their chosen invisibility. I also explored the meaning of being Armenian in Lebanon, and how descendants of the genocide negotiate their everyday and memories of the past in a country where their ancestors fled the killings in Turkey. Further, I ask how Armenians in Lebanon negotiate their daily lives in a country dominated by 16 sects.